Individual Variation Exists Within the Psychological Response to Hypoxic Bed Rest: A Retrospective Analysis - Tobita, Kunihito; Mekjavic, Igor B.; McDonnell, Adam C. (Frontiers in Physiology, 2022)
Individual variation if of interest to Space Agency’s, which cannot be explored with astronauts due to anonymity. We retrospectively analysed data collected throughout three projects (LunHab:10-day male, PlanHab: 21-day male and FemHab: 10-day female) to elucidate the potentially masked individual variation in the psychological responses to bed rest. The Profile of Mood State (POMS) and Positive and Negative Affect Schedule (PANAS) - instruments used to asses psychological state - and Lake Louise Mountain Sickness (LLMS) scores were collected prior to, following and throughout three interventions: 1: normoxic bed rest 2: hypoxic bed rest and 3: hypoxic ambulatory confinement. Total Mood Disturbance (TMD) was calculated from the POMS results, positive affect (PA) and negative affect (NA) from PANAS. The 3 instruments were included in a latent class mixed model. TMD, NA and LLMS were included in a 4-class model, with each class representing a specific type of response (Class 1: descending, Class 2: flat, Class 3: somewhat flat, Class 4: ascending). Responses for PA were assigned only to two classes (Classes 1 and 2). 54.55% or 24 participants were included in Class 2 (TMD, NA and LLMS), where the responses did not change and neither hypoxia or activity level had a significant effect on emotional state. The remaining participants were allotted to Class 1, 3 or 4, where hypoxia was a significant covariate, while activity (bed rest) was significant only for class 3. For PA, 84.09% or 37 participants were assigned to class 2 indicating a significant effect of hypoxia on the participants responses with no effect of physical activity. Class 1 participants (n=7) were not affected by hypoxia, however, physical activity improved their PA. Participants undergoing confinement, hypoxia and bed rest do not exhibit a uniform emotional response and may be categorised into 2 to 4 distinct classes. These results indicate significant individual emotional responses, that may be masked and underreported by traditional statistical approaches like means ± SD. The emotional state of our participants is a complex construct likely influenced by past experiences and different coping mechanisms which allowed some to adapt to the experimental environment more readily.